Life on the Malecón : Children and Youth on the Streets of Santo Domingo - Wolseth, Jon, 1975- (Book collections on Project MUSE., 2014)
This is a narrative ethnography of the lives of street children and youth living in Santo Domingo, Dominican Republic, and the non-governmental organizations that provide social services for them. Writing from the perspective of an anthropologist working as a street educator with a child welfare organization, the author follows the intersecting lives of children, the institutions they come into contact with, and the relationships they have with each other, their families, and organization workers. Often socioeconomic conditions push these children to move from their homes to the streets, but sometimes they themselves may choose the allure of the perceived freedoms and opportunities that street life has to offer. What they find, instead, is violence, disease, and exploitation - the daily reality through which they learn to maneuver and survive. The author describes the stresses, rewards, and failures of the organizations and educators who devote their resources to working with this population. The portrait of Santo Domingo's street children and youth population that emerges is of a diverse community with variations that may be partly related to skin color, gender, and class. The conditions for these youth are changing as the economy of the Dominican Republic changes. Although the children at the core of this book live and sleep on avenues and plazas and in abandoned city buildings, they are not necessarily glue- and solvent-sniffing beggars, or petty thieves on the margins of society. Instead, they hold a key position in the service sector of an economy centered on tourism. This book offers a window into the complex relationships children and youth construct in the course of mapping out their social environment. Using a child-centered approach, the author focuses on the social lives of the children by relating the stories that they themselves tell as well as the activities he observes. -- Provided by publisher.